The Influence of EFL Students’ Socioeconomic Background on English Learning Motivation: A Lesson from Rural Indonesian High Schools - Sholihatuddina, Nurus; Mirizon, Soni; Mirizon, Amrullah (Journal of Language and Literature Studies, 2026)
Motivation is a critical factor in English language acquisition, and its significance is widely acknowledged. However, disparities in income and resources, particularly in rural schools, strongly affect how motivated students feel. Socioeconomic status (SES) is recognized as a factor that influences academic achievement. The effect of SES on students’ motivation to learn English in rural Indonesia has not been widely studied. This study aims to investigate how socioeconomic status (SES) influences students' English learning motivation. This study used a qualitative case study method with 15 participants, selected and grouped according to the Modified Kuppuswamy Scale. This qualitative case study looks at how SES influences the motivation of students at a senior high school in a rural area. Data were collected through semi-structured interviews and analyzed using thematic analysis, employing Bourdieu’s (1986) concepts of cultural capital and habitus, as well as Gardner and Lambert’s (1972) Socio-Educational Model of Second Language Acquisition. The findings suggest that SES does not directly influence motivation. Instead, SES affects motivation indirectly through access to learning resources, family support, self-confidence, and social perception. Despite limited resources, students from lower socioeconomic backgrounds frequently remain motivated by aspirations for improved future opportunities. The study demonstrates that students who possess personal agency and receive support from teachers are more capable of addressing economic challenges. The findings further recommend the implementation of inclusive teaching methods and ensuring equitable access to resources for rural learners.